2009
DOI: 10.1007/s10265-008-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of changes in the nuclear phase and evaluation of male germ units by flow cytometry during in vitro pollen tube growth in Alstroemeria aurea

Abstract: This study aimed to analyze male gamete behavior from mature pollen to pollen tube growth in the bicellular pollen species Alstroemeria aurea. For mature pollen, pollen protoplasts were examined using flow cytometry. The protoplasts showed two peaks of DNA content at 1C and 1.90C. Flow cytometry of pollen tubes at different developmental stages that were cultured in vitro revealed changes in the nuclear phase at 9 h and 18 h after culture. Sperm cell formation occurred at 6-9 h after culture, indicating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…That the proportion of 3C DNA did not change (Table 1) suggests that no changes in MGU were detected by flow cytometer from 12 to 36 h of culture. Isolated paired sperm cells from pollen grains often separate in buffer solution (Zhang et al 1998), and a similar phenomenon occurred in our previous study on FCM analysis of pollen tubes (Hirano and Hoshino 2009). Therefore, some MGUs appear to dissociate into individual cells and nuclei, or into vegetative nucleus and pair of sperm cells during isolation or in the extraction buffer used for FCM.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…That the proportion of 3C DNA did not change (Table 1) suggests that no changes in MGU were detected by flow cytometer from 12 to 36 h of culture. Isolated paired sperm cells from pollen grains often separate in buffer solution (Zhang et al 1998), and a similar phenomenon occurred in our previous study on FCM analysis of pollen tubes (Hirano and Hoshino 2009). Therefore, some MGUs appear to dissociate into individual cells and nuclei, or into vegetative nucleus and pair of sperm cells during isolation or in the extraction buffer used for FCM.…”
Section: Discussionsupporting
confidence: 82%
“…Since the FCM-based method for analyzing pollen tubes could be applied to A. aurea (Hirano and Hoshino 2009) and C. mackenii, we believe that this method may be applicable for the analysis of pollen tubes of other species, as well, and has the potential to be used as a high throughput technique for preparing MGU material for molecular approaches in combination with a cell-sorting system. In the present study, we detected two kinds of sperm dimorphisms in terms of nuclear shape and microtubule accumulation and prior work has indicated that microtubules play a role in cell shaping, cell polarity determination, and vesicular transport (Southworth and Cresti 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations